Using electronic health records for clinical pharmacology research: Challenges and considerations - Eissa Jafari; Marisa H. Blackman; Jason H. Karnes; Sara L. Van Driest; Dana C. Crawford; Leena Choi; Caitrin W. McDonough (Wiley, 2024)
Abstract Electronic health records (EHRs) contain a vast array of phenotypic data on large numbers of individuals, often collected over decades. Due to the wealth of information, EHR data have emerged as a powerful resource to make first discoveries and identify disparities in our healthcare system. While the number of EHR‐based studies has exploded in recent years, most of these studies are directed at associations with disease rather than pharmacotherapeutic outcomes, such as drug response or adverse drug reactions. This is largely due to challenges specific to deriving drug‐related phenotypes from the EHR. There is great potential for EHR‐based discovery in clinical pharmacology research, and there is a critical need to address specific challenges related to accurate and reproducible derivation of drug‐related phenotypes from the EHR. This review provides a detailed evaluation of challenges and considerations for deriving drug‐related data from EHRs. We provide an examination of EHR‐based computable phenotypes and discuss cutting‐edge approaches to map medication information for clinical pharmacology research, including medication‐based computable phenotypes and natural language processing. We also discuss additional considerations such as data structure, heterogeneity and missing data, rare phenotypes, and diversity within the EHR. By further understanding the complexities associated with conducting clinical pharmacology research using EHR‐based data, investigators will be better equipped to design thoughtful studies with more reproducible results. Progress in utilizing EHRs for clinical pharmacology research should lead to significant advances in our ability to understand differential drug response and predict adverse drug reactions.